TEKNIK VOLTAMETRI PELUCUTAN ANODIK UNTUK PENENTUAN KADAR LOGAM Cu(II) PADA AIR LAUT PELABUHAN BENOA - Irdhawati, Irdhawati; Sahara, Emmy; Hermawan, I Wayan (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016DO - 10.24843/JCHEM.2016.v10.i01.p11, 2016)
In this research, determination of Cu(II) using anodic stripping voltammetry were conducted by measuring the current peak of Cu(II) standard solution and the concentration of the metals in the seawater around Benoa Port. Deposition time and scan rate was optimized before validation. Parameters of the method validation examined were linear range concentration, limit of detection, repeatability, and % recovery. Seawater samples were collected from two different locations, which were Dermaga Ikan Tuna and Dermaga 2. The result showed the optimum deposition time and scan rate were 540 s and 7 mV/s. Linear range concentrations were 50 to 1000 ppb with correlation coefficient of 0,9998 and the detection limit of 29 ppb. Horwitz Ratio (HorRat) factor was obtained less than 2 for repeatability measurement and percent recovery was 100.58%. The concentration of Cu(II) was found to be 188 ppb in Dermaga Ikan Tuna and 117 ppb in Dermaga 2. The concentration of Cu(II) in the seawater around Benoa Port was higher than the treshold according to Ministry of  Environment Regulation No. 51/2004 for Seawater Quality Standard.
Keywords: anodic stripping voltammetry, seawater, Cu, glassy carbon